PERAN MODAL MANUSIA, STRUKTURAL, DAN PELANGGAN DALAM MENINGKATKAN KEUNGGULAN BERSAING SERTA IMPLIKASINYA TERHADAP KINERJA ORGANISASI (Studi Pada Perusahaan Manufaktur Skala Menengah dan Besar di Provinsi Sulawesi Tengah) - Bakri Hasanuddin (Indonesian Journal of Economics and Business, 2011)
Human capital, structural, and customer are important factor in building competitive advantage and organizational performance. These capital will create wealth or value of the company. It needs therefore to pay attention especially in manufacturing companies in order to survive in the long term. It is not yet known, the description of human capital, structural and customer as well as their role in improving competitive advantage, and their implication on organizational performance, especially in medium and large scale of manufacturing companies in Central Sulawesi Province. The purpose of this study was to examine the condition of human capital, structural, and customer as well as competitive advantage and organizational performance in manufacturing firms in Central Sulawesi. And then, to test the model of these capital role both simultaneous and partially on competitive advantage and organizational performance.The research was conducted using survey method explanatory. The population of companies of medium and large scale manufacturing in Central Sulawesi is represented by one individual owners, CEO, or employees which representative of the business organizatation as respondent. The model effect was analyzed by using the Partial Least Square (PLS).The model result has a high suitability in explaining the relationship between variables. The results indicate that Human Capital, Structural Capital and Customer Capital simultaneous influence of Competitive Advantage and Organizational Performance. Partially, only the Human Capital and Structural Capital is significant both to the Competitive Advantage and Organizational Performance. In this case the Human Capital is more dominant influence on both  competitive advantage and Organizational Performance. The results showed that Customer Capital has no significant effect both for Competitive Advantage and for Organizational Performance.